A decision support system for regional hazardous waste management alternatives. Issue 1 (1998) - Amouzegar, Mahyar A.; Jacobsen, Stephen E.
Abstract : With the passage of the Resource Conservation and Recovery Act (RCRA), and the subsequent amendments to RCRA, efforts to provide tighter controls on the transportation and disposal of hazardous waste have been steadily gaining ground. This paper, intended as a decision support tool for regional planning, incorporates information on the hazardous waste generation, treatment capacity and the costs of waste treatment alternatives into an optimization problem of finding the relationship between governing agency and the toxic waste producing firms. As an example, we consider the problem of regional hazardous waste in the San Francisco Bay Area in Northern California.